High level gentamicin resistance and susceptibility to Vancomycin in enterococci in a tertiary care hospital of Dhaka City - Tamanna, Shakila; Barai, Lovely; Ahmed, AA; Haq, J Ashraful (Ibrahim Medical College Journal, 2014)
Vancomycin and high level gentamicin resistant enterococci detection is important for effective treatment and control of nosocomial infection. The present study was undertaken to determine the species distribution of Enterococcus and the rate of vancomycin and high level gentamicin resistant enterococci (HLGRE) in clinical samples in a tertiary care hospital of Dhaka city. Enterococci were identified to species level by standard biochemical and serological methods. Their susceptibilities to antibiotics were determined by disc diffusion method according to CLSI guideline. Minimum inhibitory concentration (MIC) of vancomycin and gentamicin were determined by agar dilution method. The study was conducted from July 2009 to February 2010. Among 80 isolates, 95% and 5% were identified as Enterococcus faecalis and Enterococcus faecium respectively. Out of 80 isolates 72 (90%) were sensitive and 8 (10%) were intermediate resistant to vancomycin (30?g) by disc diffusion method, but all isolates were susceptible by agar dilution MIC method. Out of 80 enterococci, 37 (46.25%) showed high level resistance to gentamicin (MIC: > 500 ?g/ml) by MIC method but, initially six of which showed sensitive result to gentamicin by disc diffusion method using 120 ?g disc. The study indicated high prevalence of HLGRE in our hospital population. MIC method was more accurate in detecting high level gentamycin resistant enterococci compared to disc diffusion method with 120 ?g gentamicin disc. However, none of the enterococcal strains showed resistance to vancomycin. HLGRE should be monitored regularly in clinical samples as it is difficult to treat. DOI: http://dx.doi.org/10.3329/imcj.v7i2.20103 Ibrahim Med. Coll. J. 2013; 7(2): 28-31